MAXIMAL FLOW MODEL AND ITS APPLICATIONS - Ahmad, Mobin (IJRDO -JOURNAL OF MATHEMATICS, 2019)
Most extreme stream issue. In the conventional most extreme stream issue, there is a capacitated arrange and the objective is to send however much of a solitary item as could be expected between two recognized hubs, without surpassing the circular segment limit limits. The issue has many applications including: shipping cargo in transportation arrange and directing liquid through a pressure driven system.